t → a lim ( t − a ) 3 ∫ a t f ( x ) d x − 2 t − a ( f ( t ) + f ( a ) ) = 0
If f ( x ) is a polynomial that satisfy the limit above for all a , then the degree of f ( x ) can at most be?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Jon Haussmann is right. Why do you have to differentiate a too? Note that we are only apply L'hopital on the limit itself, not differentiating EVERYTHING with respect to t .
Why is the limit equal to a in the first equation, then equal to 0 in the second equation?
Log in to reply
it is equal to a only please check carefully.
Log in to reply
You go from t → a lim ( t − a ) 3 ∫ a t f ( x ) d x − 2 ( t − a ) ( f ( t ) + f ( a ) ) = a to t → a lim 3 ( t − a ) 2 f ( t ) − 2 1 ( f ( t ) + f ( a ) ) − 2 ( t − a ) f ′ ( t ) = 0 by applying L'Hopital's rule, so the two limits are the same. So why is the first limit equal to a , and the second limit equal to 0?
By the way, the LaTeX code for limit is \lim.
Log in to reply
@Jon Haussmann – @Harshvardhan Mehta
@Jon Haussmann – Well just checked it now and realized that it was a typing error thanks for bringing to my notice. ⌣ ¨
You made a mistake in the third equation. It should be: t → a lim 6 ( t − a ) 2 f ( t ) − f ( a ) − ( t − a ) f ′ ( t )
This question has already appeared in JEE
This should be reported as the ans is it should be of a second degree,if it is of a single one,the numerator will be of a second degree and hence it cannot converge to a finite limit there
Problem Loading...
Note Loading...
Set Loading...
We have, t → a l im ( t − a ) 3 ∫ a t f ( x ) d x − 2 ( t − a ) ( f ( t ) + f ( a ) ) = 0
Applying L' Hospitals's rule,
⇒ t → a l im 3 ( t − a ) 2 f ( t ) − 2 1 ( f ( t ) + f ( a ) ) − 2 ( t − a ) f ′ ( t ) = 0 ⇒ t → a l im 1 2 ( t − a ) f ′ ( t ) − 2 1 ( f ( t ) + f ( a ) ) − 2 ( t − a ) f ′ ( t ) = 0 ⇒ 1 2 f ′ ′ ( t ) = 0
f ′ ′ ( a ) = 0 f o r a n y a .
⇒ f ( a ) i s a t m o s t o f d e g r e e 1 .